Cooking in caves: Palaeolithic carbonised plant food remains from Franchthi and Shanidar. (February 2023) - Kabukcu, Ceren; Hunt, Chris; Hill, Evan; Pomeroy, Emma; Reynolds, Tim; Barker, Graeme; Asouti, Eleni
Abstract: Abstract : Research on Palaeolithic hunter-gatherer diet has focused on the consumption of animals. Evidence for the use of plant foods is comparatively limited but is rapidly expanding. The authors present an analysis of carbonised macro-remains of processed plants from Franchthi Cave in the Aegean Basin and Shanidar Cave in the north-west Zagros Mountains. Microscopic examination of the charred food remains reveals the use of pounded pulses as a common ingredient in cooked plant foods. The results are discussed in the context of the regional archaeobotanical literature, leading the authors to argue that plants with bitter and astringent tastes were key ingredients of Palaeolithic cuisines in South-west Asia and the Eastern Mediterranean.